Brat – ojciec – matka. Specyfika braterstwa minoryckiego - Wiesław Block (Polonia Sacra)
The primary objective of this work is to offer a brief and orderly reflection on the way Francis of Assisi kept up fraternal life in the nascent Minorite brotherhood and on how he presents his experience of it. Although in his writings one does not come across a complete and systematic discussion on the life in the brotherhood, one can certainly find in them clear notions for identifying the particular type of evangelical life Francis envisioned. The idea of Minorite brotherhood is not limited to the community of the Friars Minor only but also extends to the whole creation, though for the most part he focuses on the relationship that has the scope of uniting the brothers from the four corners of the earth into a fellowship following in the footsteps of the poor and humble Jesus Christ. Structurally, the work is divided into two parts, the first of which describes the maturation of Francis’ attitude of being a brother (awareness of being a “brother” to entire humankind), while the second dwells upon the figure of mother, which is the prototype of fraternal relationships, according to the mind of Francis.